Plasmopara viticola the Causal Agent of Downy Mildew of Grapevine: From Its Taxonomy to Disease Management - Koledenkova, Kseniia; Esmaeel, Qassim; Jacquard, Cédric; Nowak, Jerzy; Clément, Christophe; Ait Barka, Essaid (Frontiers in Microbiology, 2022)
Plasmopara viticola (P. viticola , Berk. & M. A. Curtis; Berl. & De Toni) causing grapevine downy mildew is one of the most damaging pathogens to viticulture worldwide. Since its recognition in the middle of 19th century, this disease has spread from America to Europe and then to all grapevine-growing countries, leading to significant economic losses due to the lack of efficient disease control. In 1885 copper was found to suppress many pathogens, and is still the most effective way to control downy mildews. During the 20th century, contact and penetrating single-site fungicides have been developed for use against plant pathogens including downy mildews, but wide application has led to the appearance of pathogenic strains resistant to these treatments. Additionally, due to the negative environmental impact of chemical pesticides, the European Union restricted their use, triggering a rush to develop alternative tools such as resistant cultivars breeding, creation of new active ingredients, search for natural products and biocontrol agents that can be applied alone or in combination to kill the pathogen or mitigate its effect. This review summarize data about the history, distribution, epidemiology, taxonomy, morphology, reproduction and infection mechanisms, symptoms, host-pathogen interactions, host resistance and control of the P. viticola, with a focus on sustainable methods, especially the use of biocontrol agents.